The Language of Seafaring: Standardized Conventions and Discursive Features in Speech Communications - Bocanegra Valle, Ana (International Journal of English Studies, 2011)
This paper portrays how English language is constructed and displayed by shipboard crews and shore-based personnel when communicating through radiotelephony. Based on internationally-recognized recommendations for implementation when ships communicate with each other or with shore-based stations as well as on examples of current practice contained in marine communication manuals, this paper explores the message patterns, the standardized conventions, and the general and discursive practices governing speech communications at sea. Firstly, marine communications are defined and the role of Maritime English in the shipping industry for ensuring a safe and efficient passage discussed. Then, the standardized language of the sea is explained. Next, a move-step model to the analysis of the stages making up communicative exchanges at sea is applied and the main general and discursive features that prevail in such exchanges described. Finally, two examples help to illustrate the model and features presented and discussed.